Ukuran Perusahaan dan Kinerja Keuangan: Faktor Penting dalam Memprediksi Nilai Perusahaan - Rahma, Alya (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
The value of a company is a crucial variable considered by investors in making investment decisions. Company value can be predicted using various factors, one of which is company size and financial performance. This research aims to examine the influence of company size and financial performance on company value. The study utilizes empirical data from LQ45-listed companies on the Indonesia Stock Exchange (IDX) during the period 2018-2022. Secondary data from 16 LQ45 companies, comprising 80 financial reports, are employed as the research data source. Panel data regression analysis is used for research analysis. The research results indicate that company size and financial performance have a positive influence on company value. Company size positively affects company value because larger-sized companies tend to have higher competitive advantages. Financial performance positively influences company value because companies with strong financial performance tend to have the potential to generate greater profits for shareholders.